2022
DOI: 10.1186/s13578-022-00806-6
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acid and anacardic acid are reversible inhibitors of SARS-CoV-2 3-chymotrypsin-like protease

Abstract: Because of the emerging variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in different regions of the world, the battle with infectious coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has been seesawing. Therefore, the identification of antiviral drugs is of particular importance. In order to rapidly identify inhibitors for SARS-CoV-2 3-chymotrypsin-like protease (3CLpro), an enzyme essential for viral replication, we combined the fluorescence polarization (FP) technique with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Anacardic acid is the main component of extracts from Ginkgo biloba and Rhus verniciflua , which has a wide range of pharmacological activities such as antibacterial, anticancer, and antiviral ( Hundt et al, 2015 ; Park et al, 2018 ; Saedtler et al, 2020 ). Recent studies have confirmed that the EC 50 value of antiviral activity of anacardic acid is 9 μM in live SARS-CoV-2 virus by targeting Mpro ( Chen et al, 2021b ; Hicks et al, 2022 ; Li et al, 2022 ; Xiong et al, 2021 ; Yan et al, 2022b ). Our study demonstrated that anacardic acid is likely a novel competitive inhibitor targeting both PLpro and Mpro of SARS-CoV-2, and more in vivo experiments for its antiviral mechanism will be explored in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Anacardic acid is the main component of extracts from Ginkgo biloba and Rhus verniciflua , which has a wide range of pharmacological activities such as antibacterial, anticancer, and antiviral ( Hundt et al, 2015 ; Park et al, 2018 ; Saedtler et al, 2020 ). Recent studies have confirmed that the EC 50 value of antiviral activity of anacardic acid is 9 μM in live SARS-CoV-2 virus by targeting Mpro ( Chen et al, 2021b ; Hicks et al, 2022 ; Li et al, 2022 ; Xiong et al, 2021 ; Yan et al, 2022b ). Our study demonstrated that anacardic acid is likely a novel competitive inhibitor targeting both PLpro and Mpro of SARS-CoV-2, and more in vivo experiments for its antiviral mechanism will be explored in the future.…”
Section: Discussionmentioning
confidence: 93%
“…However, its success rate depends not only on the capacity and diversity of screened chemical libraries, but also on the robustness, convenience, and cost efficiency of the HTS assays ( Shan et al, 2021 ). As a homogenous biochemical assay, our research group has successfully utilized FP technique for screening of protein-protein interaction antagonists and Mpro inhibitors ( Chen et al, 2017 , 2021a ; Li et al, 2022 ; Yan et al, 2021 , 2022b ). At present, the discovery of PLpro inhibitors mainly relies on FRET and cell-based screening assays, but these approaches often face more obstacles in a large-scale screening.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study 18 has investigated photoprotective and anti-inflammatory activities of AA in human skin. Recently, other studies 19,20 indicated that the anacardic acid inhibit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replication in vitro at nontoxic concentrations. The results provide a novel natural product as promising SARS-CoV-2 antiviral.…”
Section: Introductionmentioning
confidence: 99%
“…The results provide a novel natural product as promising SARS-CoV-2 antiviral. 19,20 Polymer nanoparticles have become highly promising candidates for the transport and release of drugs mainly because they provide means for delivering active molecules in controlled time and site specifically. [21][22][23] Several works [24][25][26][27][28] have been developed in the preparation of polymeric nanoparticles via miniemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…GA (15:1) has a 15-carbon chain with a double bond at the C6 position of the salicylic acid. Numerous pharmacological effects of GA (15:1) have been demonstrated including the ability to inhibit protein SUMOylation, promote tumor cell apoptosis, block HIV protease activity, and act as reversible inhibitors of SARS-CoV-2 3-chymotrypsin-like protease. According to previous studies, GA (15:1) displays antibacterial and antibiofilm activities against Staphylococcus aureus, Bacillus amyloliquefaciens, Streptococcus thermophiles, and Enterococcus faecalis. , However, the influence of GA (15:1) on the growth of planktonic cells and biofilms of S. agalactiae in vitro and in vivo is yet unknown.…”
mentioning
confidence: 99%